MODELING OF THE EXTRAORDINARY EVENT CONSEQUENCES FOR THE TRANSPORT OF DANGEROUS SUBSTANCES (Perner's Contacts, 2018)
Transport of dangerous substances by road tankers entails a lot of risks. In the event of a tank accident, apart from the possibility of explosion and fire, there is a possibility of extensive damage to the environment, human life or health. This article deals with the problems of dangerous substances (especially flammable liquid substances) transport. Purpose of this article is to model the consequences of traffic accident the tanker carrying petrol and determine the negative consequences on population.
Keywords: road transport, safety factors, transport of dangerous substances, extraordinary even, modeling of consequences